2022
DOI: 10.25271/sjuoz.2022.10.3.929
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Among Athletes In Zakho City, Kurdistan Region, Iraq: Nasal Carriage Rate, Risk Factors, and Antibiotic Sensitivity Profile

Abstract: Background and aims: Staphylococcus aureus is a leading cause of infectious diseases and responsible for outbreaks among athletes’ team. The aims of this study were to determine the prevalence rate of S. aureus among athletes, and evaluate the antibiotic resistance and risk factors associated with S. aureus isolates. Materials and methods: We performed a cross-sectional study to determine the S. aureus nasal carriage rate among athletes practicing different sports. Swabs were collected from the anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Antibiotic resistance is rising to dangerously high levels worldwide (Hussein et al, 2015;Assafi et al, 2017;Abduljabar and Naqid, 2022). Taha et al (2019) and Chen et al (2022) found that S. lugdunensis isolates had high susceptibility to most antibiotics, which agrees with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Antibiotic resistance is rising to dangerously high levels worldwide (Hussein et al, 2015;Assafi et al, 2017;Abduljabar and Naqid, 2022). Taha et al (2019) and Chen et al (2022) found that S. lugdunensis isolates had high susceptibility to most antibiotics, which agrees with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Antibiotic resistance rate changes according to geographical areas due to presence of different strains in different regions of the world and variation in antibiotic use [11]. Resistance pattern of pathogens to antibiotics are continuously changing [9,[12][13][14]. Antibiotic resistance is an important medical problem and one of the World Health Organization (WHO) priorities because there is an increasing trend of antibiotic resistance world-wide making it harder to eliminate uropathogens from urinary tract which end up with longer illness and mortality rates [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted in Kurdistan Iraq about sexually transmitted diseases including infection causing problem in Genital tract[20>24] but there is no study about pornography. Despite the increase in pornography consumption during the last decade, pornography viewing differs in accordance with gender and age group [25].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of rape and violence in the world also increase in those consuming pornography about 30% (10). The rate of sexually transmitted diseases and hepatitis virus in the world including Iraq also increases among different age groups and gender [14][15][16][17][18][19] Many studies have been conducted in Kurdistan Iraq about sexually transmitted diseases including infection causing problem in Genital tract [20][21][22][23][24] but there is no study about pornography. Despite the increase in pornography consumption during the last decade, pornography viewing differs in accordance with gender and age group [25].…”
Section: Introductionmentioning
confidence: 99%